2021
DOI: 10.1111/cns.13646
|View full text |Cite
|
Sign up to set email alerts
|

Use of a panel of four microRNAs in CSF as a predicted biomarker for postoperative neoangiogenesis in moyamoya disease

Abstract: Introduction and Aims At present, the treatment for moyamoya disease (MMD) primarily consists of combined direct and indirect bypass surgery. Nevertheless, more than half of indirect bypass surgeries fail to develop good collaterals from the dura and temporal muscle. This study aimed to investigate whether microRNAs (miRNAs) in cerebrospinal fluid (CSF) could serve as biomarkers for the prediction of postoperative collateral formation. Methods Moyamoya disease patients with indirect bypass surgery were divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In previous studies, the spontaneous transdural collaterals that appear were considered the brain's ability to promote angiogenesis and served as a radiographic biomarker to predict the collaterals' development after revascularization ( 7 , 8 , 12 ). In this research, we detected that the levels of TGFβ1 were associated with the formation of transdural collaterals, indicating that TGFβ1 may become a vital biomarker in predicting collaterals after revascularization.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous studies, the spontaneous transdural collaterals that appear were considered the brain's ability to promote angiogenesis and served as a radiographic biomarker to predict the collaterals' development after revascularization ( 7 , 8 , 12 ). In this research, we detected that the levels of TGFβ1 were associated with the formation of transdural collaterals, indicating that TGFβ1 may become a vital biomarker in predicting collaterals after revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Bypass surgery is recommended as a first-line treatment of MMD, including direct bypass, indirect bypass, and combined strategies (8)(9)(10). Moreover, direct bypass surgery can immediately increase blood flow, but indirect bypass requires more time to produce angiogenesis from the muscle and dura (8,9).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Wang et al identified a novel and highly sensitive e-miRNA signature for MMD detection and explored potential targets. 16 However, differences in exosomal RNAs between patients with MMD, ICAD, and healthy controls, as well as how they affect the pathogenesis of MMD and ICAD, remain unknown.…”
Section: Introductionmentioning
confidence: 99%